Life prediction of aeroengine blade based on the random vibration fatigue under service conditions - Yang, Wenjun; Zhang, Hang; Li, Sicheng; Jin, Xingzhuo; Pan, Wujiu; Wang, Lei (Journal of mechanical science and technology, 2025)
Vibration form of aeroengine blade is often random under service conditions. For the complexity of vibration environment, current methods are still difficult to accurately predict the random vibration fatigue life of aeroengine blade. Considering the effects of spectral width coefficient on error function, this research has successfully developed the modified Chaudhury-Dove model and achieved the life prediction of aeroengine blade under service conditions. Firstly, typical u-notched specimen is taken as the simulated blade, and distribution characteristics of stress response and fatigue life are discussed at different error coefficients. Then calculation results are compared with different frequency domain models, the optimum error coefficient is determined for the modified Chaudhury-Dove model. Finally, fatigue life of aeroengine blade is successfully predicted under the service conditions, and the effects of signal intensity and direction are discussed on the random vibration response. The results show there is a much higher precision for the modified Chaudhury-Dove model, when the bandwidth coefficient η is less than 0.14 and the error coefficient erf ( x ) is equal to 0.7. Response stress peak of blade root is the largest at the basic frequency, fatigue life decreases obviously with the intensity increase of excitation signal, and fatigue damage is the greatest when excitation signal is circumferential excitation. The research has an important engineering significance, and provides the guidance for random vibration fatigue life prediction of aeroengine blade under the service conditions.